Islamization in Malay Archipelago: A Study of the Historical Philosophy Analysis of Syed Muhammad Naquib Al-Attas - Mulyadi Mulyadi (Al-Widad, 2025)
The purpose of this research was to reveal the view of Syed Muhammad Naquib Al-Attas about the Islamization in Malay Archipelago. In this research, Al-Attas, as one of the world intellectuals of Malay Archipelago, tried to reconstruct the ideas of western scholars who tended to restrict the role of Islam and accentuate the significance of Hinduism and Buddhism in the Islamic history and culture in Malay Archipelago. The western scholars supported Hinduism and Buddhism as the most influential religions in Malay Archipelago instead of the influence of Islam. The argument was proved by the various relics of stone carvings, statues, and temples. The argument of the western scholars seemed to reduce the role of Islam as the largest religion embraced by people of Archipelago for centuries. Some of western scholars whose views would be clarified by Al-Attas were Van Leur, Schrike, Snouck Hurgronje, and Winstedt. Al-Attas provided an argument with facts and data that it was the role of Islam through Sufism metaphysics and Arabic language of Malay Archipelago that shaped, changed, and became the view of people’s life in Malay Archipelago. It should be emphasized here that Islamization was a theory initiated by Al-Attas to confirm the influence of Islam in Malay Archipelago through the concept of Sufism metaphysics.